The Effect of Gender and Ethnicity and their Intersection on Work Satisfaction and Earnings in Estonia, 1993-2008 - Hansson, Leeni; Aavik, Kadri (Studies of Transition States and Societies, 2012)
This article examines trends in the labour market position, deﬁ ned in terms of three dimensions – earnings, perceived job security and overall job satisfaction – among four population groups in Estonia – Estonian men and women and Russian-speaking men and women. We explore how the labour market position of these groups changed between 1993 and 2008.We used data from 1993 and 2008, collected in the population survey Work, Family and Leisure, designed by the Institute of International and Social Studies at Tallinn University. We carried out a two-step analysis: ﬁ rst, we conducted descriptive analysis to explore changes in the labour market situation of men and women of two ethnic groups in the period of 1993-2008; and second, we used models of multivariate analysis of variances to examine how gender, ethnicity and occupational status as well as the intersection of these variables are related to earnings, job security and job satisfaction.We found that Estonian men have emerged as the most successful group in the labour market, while the labour market position of Russian-speaking women is the most disadvantaged compared to other groups in terms of earnings, job security and job satisfaction. We suggest that these labour market inequalities could be increasing, and that the interaction of gender and ethnicity might become increasingly important in shaping labour market outcomes.